Estimating Groundwater Recharge for Sustainable Management in the Nigerian Sector of the Chad Basin - Goni, I.B.; Edmunds, W.M.; Adeniji, F.A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
Groundwater is the perennial source of water supply for domestic and other applications in the Nigerian sector of the Chad basin. Therefore, quantifying the current rate of recharge is fundamental to sustainable management of the resource. The chloride (Cl) mass balance technique was used to estimate the rate of recharge. Average Cl concentrations in rainfall from three stations over eight years were used as input data. Eight unsaturated zone Cl profiles were obtained and Cl concentrations in the groundwater were measured for over 400 samples from wells and boreholes. An average recharge rate of 41 mm per annum was estimated from the unsaturated zone profiles. The regional rate obtained using Cl concentrations in groundwater is slightly higher, estimated at 48 mm per ammum, which is attributable to other mechanisms of recharge such as river channels, pools, depressions and regional flow that bypass the unsaturated zone. The estimated recharge to the shallow groundwater in this region is considerable and can sustain present day abstractions. The observed decline in water table in recent years is largely due to reduced rainfall during the Sahel drought and consequent reduction in recharge, although human impacts are also identified as is common with most semi-arid areas of the world. Although the flood plains aquifers (fadamas) are probably fully recharged annually through river channels, caution must be exercised in introducing irrigation schemes. Any agricultural development should be preceded by detailed studies, so as to utilise the quantity of water that is recharged annually and must also adopt water saving techniques.